Reconfiguring - Louis Klein, Adam (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Adam Louis Klein Title (English): Reconfiguring Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 84 Page Count: 1 Citation (English): Adam Louis Klein, “Reconfiguring,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 84.